1982
DOI: 10.1159/000110696
|View full text |Cite
|
Sign up to set email alerts
|

Research Protocol for Measuring the Prevalence of Neurologic Disorders in Developing Countries

Abstract: Because of the scarcity of trained personnel in neurology in developing countries, we designed a protocol utilizing, in large part, non-doctor primary health care personnel for collecting data in a door-to-door survey to determine the prevalence of major neurologic diseases. A pilot study revealed the feasibility of a census, screening questionnaire, and simple neurologic examination successfully administered to 903 subjects in a rural community in Nigeria by non-doctor health care workers. Of 236 who were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
121
3

Year Published

1988
1988
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(138 citation statements)
references
References 14 publications
13
121
3
Order By: Relevance
“…In recent years, many prevalence studies have been reported from developing countries with the same methods suggested by WHO. Some of the prevalence rates reported from rural areas of developing countries are as follows: 5.8/1,000 in Guatemala (lo), 10.2/1,000 in Tanzania ( 1 l), 2.47/1,000 in Kashmir, India (12), 57/1,0OO in the Guaymi Indian population of Panama (13), and 37/1,000 in Nigeria (14). In general, population-based WHO protocol studies have given an average prevalence rate of 18.5/1,000 (6).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many prevalence studies have been reported from developing countries with the same methods suggested by WHO. Some of the prevalence rates reported from rural areas of developing countries are as follows: 5.8/1,000 in Guatemala (lo), 10.2/1,000 in Tanzania ( 1 l), 2.47/1,000 in Kashmir, India (12), 57/1,0OO in the Guaymi Indian population of Panama (13), and 37/1,000 in Nigeria (14). In general, population-based WHO protocol studies have given an average prevalence rate of 18.5/1,000 (6).…”
Section: Discussionmentioning
confidence: 99%
“…The urban population according to the national census (IBGE) 18 is 336000 inhabitants where 51.3% are women. The distribution in percentages of the inhabitants for the age groups (years) is 7.3% (0-4), 17.3% (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), 68.8% , and 6.6% (65 or over).…”
Section: Methodsmentioning
confidence: 99%
“…oping countries, as quality of data required may not be available in the form of medical records 4,8,[10][11][12][13][14][15] . Brazil is a country of continental dimension located in South America with approximately 170 millions inhabitants.…”
mentioning
confidence: 99%
“…The crude prevalence ratios / 100,000 for stroke in 3 community-based studies in Nigeria were 58, 60, 400 (16,17,68) and 15 in Ethiopia (12) ( Table 4). The low prevalence ratios could be explained by high annual mortality rate of stroke as was found in one Nigerian community (17) where age-adjusted (to USA population) annual mortality rate for stroke exceeded that of the USA.…”
Section: Prevalencementioning
confidence: 99%